A Powerful Nanocomposite Polymer Prepared From Metal Oxide Nanoparticles Synthesized via Brown Algae as Anti-corrosion and Anti-biofilm - Sadek, Rawia F.; Farrag, Hala A.; Abdelsalam, Shimaa M.; Keiralla, ZMH; Raafat, Amany I.; Araby, Eman (Frontiers in Materials, 2019)
The chemical/microbial bio-corrosion in water pipelines are the most common problem in industry worldwide which cause damage to expensive equipment and increases the maintenance costs. In this work, the green synthesis of nanocomposite was synthesized using brown algae (Sargassum muticum) extract. This method is eco-friendly and non-toxic. The synthesized nanocomposite was characterized using UV–vis spectroscopy, Dynamic light scattering (DLS), X-ray diffraction (XRD), Transmission electron microscopy (TEM) and FTIR analysis. The size of ZnO and CuO nanoparticles was reduced to 15nm and 20 nm respectively, after exposure to 60Co gamma-ray irradiation. The nanocomposite showed significant P-value (P<0.001) as a biofilm inhibitor and anti-adherence for Proteus mirabilis, Pseudomonas aeruginosa and Staphylococcus aureus, which were represented bio-corrosion index. The results of weight loss method showed that Proteus mirabilis caused the highest bio-corrosion rate (1.5 mpy) on mild steel coupon as examined by SEM. The nanocomposite prevented the adhesion of biofilm bacteria to carbon mild steel coupon which was confirmed by SEM examination. Finally, the nanocomposite showed highest anti-corrosion efficacy in 1M HCl at 150 ppm with high anti-corrosion efficiency (92.3%). The results of this study concludes that the green synthesized nanocomposite has multi-function to be used as anti-bacterial, anti-biofilm, anti-corrosion and anti-bio corrosion.